The Influence of Service Quality, Facilities and Prices on Consumer Satisfaction at the Dawideva Tailor's Sewing Business of Silangkitang - Nurhasmaliza Siregar; Novrihan Leily Nasution; Raja Saul Marto Hendry (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to determine the effect of service quality, facilities and prices on customer satisfaction at DawiDeva Tailor Silangkitang. The research method used in this research is descriptive quantitative. The data analysis used in this study is the classical assumption test, multiple linear regression analysis, hypothesis testing, F test (simultaneously), and R2 test. The population in this study were all customers of DawiDeva Tailor. The determination of the number of samples in the study cannot be known with certainty, so the sample size can be calculated using the MOE formula. Adjuster R Square value is 0.593 with this multiple determination test from the calculation of multiple linear regression the coefficient of determination is 0.770 x 100% of 77.0%. Whereas the variables of Service Quality, Facilities, and Prices on Consumer Satisfaction are 77.